THE ART OF DECORATIVE EMBROIDERY ON AO DAI IN HO CHI MINH CITY (Proceeding of the International Conference on Arts and Humanities, 2023)
The Ao Dai is considered the Vietnamese traditional national costume because the shape structure of the Ao Dai is a special shape that does not coincide with any other type of costume in the world today, and at the same time creates a graceful look, highlighting the beauty of the three body curves of a woman is the dominant feature of the Ao Dai. Therefore, the shaping of embroidered motifs to decorate Ao Dai contributes to increasing the beauty of this female costume, and at the same time promotes the traditional art of embroidery and decoration of the Vietnamese nation. The characteristics of decorative embroidery on Ao Dai are specifically shown through designs, colors, materials, and patterns arranged in a harmonious way to create a beautiful layout on the Ao Dai, which further proves the historical value and the core values of decorative embroidery on Ao Dai developed according to the divergence of Vietnamese history in general, especially in Ho Chi Minh City in particular. Today, the modern embroidery styles with diverse embroidery techniques, patterns, textures close to life, and rich colors, are closer and more pervasive in all types of traditional ao dai Vietnam, through their use values such as Ao dai embroidered for festivals, performances, gala dinners and especially Ao dai embroidered with daily wear, contributing to meeting the aesthetic needs of women in Ho Chi Minh City.
Keywords: Ao Dai; embroidery Ao Dai; embroidery motif; decorative embroidery art; Embridery stitch